A sustainability comparison between drilling and milling for hole-enlargement in machining of hardened steels. Issue 5 (3rd September 2019) - Iqbal, Asif; Suhaimi, Hazwani; He, Ning
Abstract: Hole-making is one of the most important processes of metal shaping domain. Although, drilling is a commonly used approach to cut holes in metallic parts, the process cannot be completed with the cutting action of one drill bit if the work material is hard and diameter of the hole is large. Usually, a drill having diameter equal to the required diameter of the hole is utilized to enlarge a predrilled hole of a smaller diameter. In this work, we have investigated sustainability of using another method of enlarging a pre-drilled hole, namely side and end milling and compared it with the drilling-based approach. The work material used in the study is a high carbon steel, which is heat-treated to two distinct levels of surface hardness. Besides process type and work material hardness, the other two parameters tested in the investigation are cutting speed and depth of hole. A total of 16 experiments were performed to generate data regarding the sustainability measures, namely hole surface roughness, specific cutting energy and tool wear. Process choice (drilling or milling) for hole-enlargement was found to possess a significant effect on all the measured responses. Analyses carried out on the experimental data revealed that although the drilling-based option led to an immensely better surface finish, the milling-based option performed better with respect to the other measures of economic and environmental sustainability.